Scaling laws under quantum Hall effect for a smooth disorder potential - Gudina, S.V.; Klepikova, A.S.; Neverov, V.N.; Shelushinina, N.G.; Yakunin, M.V. (Физика низких температур, 2019)
We carried out the analysis of discovered experimental values of the critical parameter κ for the quantum Hall plateau-plateau transitions in modulation-doped GaAs/AlGaAs heterostructures. It turned out that these values are in the main concentrated at the range of 0.5–0.7. We argue that within the theoretical concepts for the largescale disorder potential, it corresponds to a borderland between quantum tunnelling processes and classical percolation regime. Just, the critical exponent value for the bandwidth of delocalized states, κ = 0.54 ± 0.01, obtained by us for HgTe-based heterostructure with inverted band spectrum, can be associated with a smooth character of impurity potential in our system